Combining morphology and molecular data to improve Drosophila paulistorum (Diptera, Drosophilidae) taxonomic status. Issue 2 (3rd April 2018) - Zanini, Rebeca; Müller, Mário Josias; Vieira, Gilberto Cavalheiro; Valiati, Victor Hugo; Deprá, Maríndia; Valente, Vera Lúcia da Silva
ABSTRACT: The willistoni species subgroup has been the subject of several studies since the latter half of the past century and is considered a Neotropical model for evolutionary studies, given the many levels of reproductive isolation and different evolutionary stages occurring within them. Here we present for the first time a phylogenetic reconstruction combining morphological characters and molecular data obtained from 8 gene fragments (C OI, COII, Cytb, Adh, Ddc, Hb, kl-3 and per ). Some relationships were incongruent when comparing morphological and molecular data. Also, morphological data presented some unresolved polytomies, which could reflect the very recent divergence of the subgroup. The total evidence phylogenetic reconstruction presented well-supported relationships and summarized the results of all analyses. The diversification of the willistoni subgroup began about 7.3 Ma with the split of D. insularis while D.paulistorum complex has a much more recent diversification history, which began about 2.1 Ma and apparently has not completed the speciation process, since the average time to sister species separation is one million years, and some entities of the D. paulistorum complex diverge between 0.3 and 1 Ma. Based on the obtained data, we propose the categorization of the former "semispecies" of D. paulistorum as a subspecies and describe the subspecies D. paulistorum amazonian, D. paulistorum andeanbrazilian, D. paulistorum centroamerican, D. paulistorum interior, D. paulistorum orinocan and D. paulistorum transitional.